Maestros cántabros en la Guerra Civil: La represión en cascada. // Teachers Cantabrians in the Civil War: Repression cascade. - Enrique Gudín de la Lama (Cabás)
(ES) Durante la guerra civil española Cantabria pasó un año en el bando del gobierno, antes de ser ocupada por las tropas franquistas. Durante ese año, los maestros fueron sometidos a un proceso depurativo. Cuando la provincia cambió de manos, los maestros tuvieron que soportar un nuevo proceso depurativo al que se sumaron, en muchos casos, sucesivos procesos judiciales fruto del entramado legal y jurídico que se estableció en aquellos años. // (EN) Throughout the Spanish Civil War, before Cantabria had been occupied by Francos's troops, it spent a year on the government side. During that year, teachers were subjected to a purifying process. When the county passed into Franco's hands, teachers had to bear a new depurative process which was joined in many cases by successive judicial persecutions as a result of the legal and judiciary framework that was established on those years.